Production of Moringa based Food Flavouring with the Addition of Dried Shrimp - Sebastianus Charmie Wadjong; Mohammad Prasanto Bimantio; Maria Ulfah (International Journal of Food Sciences and Nutrition Innovations, 2026)
Background: Moringa leaves, rich in essential nutrients like calcium, protein, and antioxidants, are widely valued for their health benefits. However, due to their natural bitterness and strong aroma, they are commonly consumed as capsules or teas rather than incorporated into everyday meals, limiting their market reach.Aim: To increase consumer acceptance, especially among children and adults seeking nutritious foods, "Bon Kelor" was developed as a moringa-based food flavouring with added dried shrimp to enhance both flavour and nutritional value. This study aimed to evaluate the effects of blanching time and dried shrimp addition on the nutritional and sensory qualities of "Bon Kelor" and to determine the most favourable formulation.Methods: The research used a Complete Block Design with two factors: blanching time (1, 3, and 5 minutes) and dried shrimp concentration (5%, 10%, and 15%). The products were assessed for yield, moisture, ash, fibre, protein, calcium, and organoleptic characteristics such as aroma, colour, and taste.Result:  Blanching time significantly affected water, ash, and fibre content, as well as taste, while dried shrimp addition notably increased ash, fibre, protein, and calcium levels. The optimal formulation, based on overall liking among panellists, featured a blanching time of 5 minutes and a dried shrimp concentration of 15%, yielding a balanced nutritional profile and improved taste.Conclusion: This formulation had a moisture 5.85%, ash 16.64%, fibre 14.04%, protein 21.89%, and calcium 74.41 ppm.